2000
DOI: 10.1046/j.1432-1327.2000.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of yeast fatty acid synthase

Abstract: The prosthetic group of yeast fatty acid synthase (FAS), 4'-phosphopantetheine, is covalently linked to Ser180 of subunit alpha. It originates from coenzyme A and is transferred to the enzyme by a specific phosphopantetheine:protein transferase (PPTase). The present study demonstrates that the FAS-activating PPTase of yeast represents a distinct catalytic domain of the FAS complex and resides within the C-terminal portion of subunit alpha. The autoactivation capacity of yeast FAS became evident from in vitro p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 25 publications
1
47
0
1
Order By: Relevance
“…The well characterized Sfp exhibits an extraordinarily broad substrate specificity and could modify all acyl carrier protein substrates tested, including PCPs of NRPS as well as ACPs of FAS and PKS. The third group is an integrated PPTase found as the C-terminal domain of the multifunctional FAS2, for example in Saccharomyces cerevisiae (7). This classification has recently been further supported by structural studies.…”
Section: ј-Phosphopantetheine (Ppant)mentioning
confidence: 87%
“…The well characterized Sfp exhibits an extraordinarily broad substrate specificity and could modify all acyl carrier protein substrates tested, including PCPs of NRPS as well as ACPs of FAS and PKS. The third group is an integrated PPTase found as the C-terminal domain of the multifunctional FAS2, for example in Saccharomyces cerevisiae (7). This classification has recently been further supported by structural studies.…”
Section: ј-Phosphopantetheine (Ppant)mentioning
confidence: 87%
“…Although class 2 PPTs are monomers consisting of two domains, structural comparison between class 1 and 2 PPTs has demonstrated that they have comparable domain architecture despite the lack of sequence similarity (30). Class 3 PPTs are distinct in that they constitute a specific enzymatic domain integrated within a larger, multifunctional protein, and the PPT of FAS2 in Saccharomyces cerevisiae is the prototypical example (31).…”
Section: Discussionmentioning
confidence: 99%
“…Sfp has proven to recognize every CP tested so far, including PCPs of NRPSs and ACPs of FASs and PKSs. PPTases of the third group act as integrated domains on their cognate ACP of type I FAS, as is the case in Saccharomyces cerevisiae, for example (11) (Fig. 2).…”
mentioning
confidence: 98%